The impact of perceived ethical leadership of supervisors on graduate students' creativity: The mediating role of psychological empowerment - Yang, Yan; Huang, Jian-Hao (Edelweiss Applied Science and Technology, 2025)
Creativity has become a vital metric for assessing the quality of talent development. This study aims to analyze the impact of supervisors on graduate students' creativity and to uncover the role of psychological empowerment in this process. Based on cognitive evaluation theory, this empirical study investigates the impact of perceived ethical leadership of supervisors on graduate students' creativity, as well as the mediating role of psychological empowerment. Data were collected using an online questionnaire distributed via the Questionnaire Star platform. The sample comprised master's and doctoral students from four universities in southwestern China. A total of 1,011 questionnaires were distributed, and 139 were excluded due to non-compliance with the research criteria, resulting in 872 valid responses. Results indicate that the perceived ethical leadership of supervisors enhances graduate students' creativity. Furthermore, psychological empowerment fully mediates the relationship between the perceived ethical leadership of supervisors and graduate students' creativity. Enhancing supervisors' ethical leadership could effectively improve graduate students' creativity.